Visualizing macroscopic inhomogeneities in perovskite solar cells - Dasgupta, A; Mahesh, S; Caprioglio, P; Lin, Y-H; Zaininger, K-A; Oliver, RDJ; Holzhey, P; Zhou, S; McCarthy, MM; Smith, JA; Frenzel, M; Christoforo, MG; et al. (American Chemical Society, 2022)
Despite the incredible progress made, the highest efficiency perovskite solar cells are still restricted to small areas (<1 cm2). In large part, this stems from a poor understanding of the widespread spatial heterogeneity in devices. Conventional techniques to assess heterogeneities can be time consuming, operate only at microscopic length scales, and demand specialized equipment. We overcome these limitations by using luminescence imaging to reveal large, millimeter-scale heterogeneities in the inferred electronic properties. We determine spatially resolved maps of “charge collection quality”, measured using the ratio of photoluminescence intensity at open and short circuit. We apply these methods to quantify the inhomogeneities introduced by a wide range of transport layers, thereby ranking them by suitability for upscaling. We reveal that top-contacting transport layers are the dominant source of heterogeneity in the multilayer material stack. We suggest that this methodology can be used to accelerate the development of highly efficient, large-area modules, especially through high-throughput experimentation.